Driving agricultural innovation: Gurpreet Singh Sidhu’s contribution to sustainable farming in Punjab - Singh, Vinay; Singh, Gurdeep; Singh, Pritpal (Indian Farming, 2025)
Punjab’s rice-wheat cropping system (RWCS) is confronting significant environmental challenges, including groundwater depletion, soil degradation and air pollution. S. Gurpreet Singh Sidhu, a visionary farmer from Mehraj village, Bathinda has emerged as a champion of sustainable agricultural practices by adopting resource conservation technologies viz. direct seeded rice (DSR) and Happy Seeder technology for wheat establishment. These innovative practices have led to substantial improvements in soil health, reductions in water and input costs, and enhanced crop yields. He has achieved substantial resource conservation with up to 28% saving in irrigation water and 37.3% in diesel fuel consumption, besides noteworthy improvement in soil health manifested as increase in organic carbon by 43.8%. While horizontally extending these technologies across 12 adjoining villages, he has engraved technological footprints over 261 hectares under DSR and 286 hectares to in situ rice residue management before wheat establishment. Furthermore, his establishment of a custom hiring center (CHC) has provided small farmers with affordable access to innovative machinery, while amplifying the reach and impact of sustainable crop production practices. Widely recognized for his contributions with both national and international accolades, he exemplifies the potential of innovative solutions to reconcile agricultural productivity with environmental conservation. His efforts serve as a powerful model for sustainable agricultural development, offering inspiration for a greener, more efficient agricultural future.